Antiplasmodial and anti-inflammatory effects of an antimalarial remedy from the Wayana Amerindians, French Guiana: Takamalaimë (Psidium acutangulum Mart. ex DC., Myrtaceae). (26th May 2015) - Houël, Emeline; Fleury, Marie; Odonne, Guillaume; Nardella, Flore; Bourdy, Geneviève; Vonthron-Sénécheau, Catherine; Villa, Pascal; Obrecht, Adeline; Eparvier, Véronique; Deharo, Eric; Stien, Didier
Abstract: Ethnopharmacological relevance: Field investigations highlighted the use of Psidium acutangulum Mart. ex DC (syn. P. persoonii McVaugh), a small tree used by the Wayana Amerindians in Twenke–Taluhwen and Antecume–Pata, French Guiana, for the treatment of malaria, and administered either orally in the form of a decoction or applied externally over the whole body. This use appears limited to the Wayana cultural group in French Guiana and has never been reported anywhere else. Our goal was to evaluate the antimalarial and anti-inflammatory activities of a P. acutangulum decoction to explain the good reputation of this remedy. Materials and methods: Interviews with the Wayana inhabitants of Twenke–Taluhwen and Antecume–Pata were conducted within the TRAMAZ project according to the TRAMIL methodology, which is based on a quantitative and qualitative analysis of medicinal plant uses. A decoction of dried aerial parts of P. acutangulum was prepared in consistency with the Wayana recipe. In vitro antiplasmodial assays were performed on chloroquine-resistant FcB1 ([ 3 H]-hypoxanthine bioassay) and 7G8 (pLDH bioassay) P. falciparum strains and on chloroquine sensitive NF54 ([ 3 H]-hypoxanthine bioassay) P. falciparum strain. In vitro anti-inflammatory activity (IL-1β, IL-6, IL-8, TNFα) was evaluated on LPS-stimulated human PBMC and NO secretion inhibition was measured on LPS stimulated RAW murine macrophages. Cytotoxicity of the decoction was measured on L6 mammalian cells, PBMCs, and RAW cells. A preliminary evaluation of the in vivo antimalarial activity of the decoction, administered orally twice daily, was assessed by the classical four-day suppressive test against P. berghei NK65 in mice. Results: The decoction displayed a good antiplasmodial activity in vitro against the three tested strains, regardless to the bioassay used, with IC50 values of 3.3 µg/mL and 10.3 µg/mL against P. falciparum FcB1 and NF54, respectively and 19.0 µg/mL against P. falciparum 7G8. It also exhibited significant anti-inflammatory activity in vitro in a dose dependent manner. At a concentration of 50 µg/mL, the decoction inhibited the secretion of the following pro-inflammatory cytokines: TNFα (−18%), IL-1β (−58%), IL-6 (−32%), IL-8 (−21%). It also exhibited a mild NO secretion inhibition (−13%) at the same concentration. The decoction was non-cytotoxic against L6 cells (IC50 >100 µg/mL), RAW cells and PBMC. In vivo, 150 µL of the decoction given orally twice a day (equivalent to 350 mg/kg/day of dried extract) inhibited 39.7% average parasite growth, with more than 50% of inhibition in three mice over five. The absence of response for the two remaining mice, however, induced a strong standard deviation. Conclusions: This study highlighted the in vitro antiplasmodial activity of the decoction of P. acutangulum aerial parts, used by Wayana Amerindians from the Upper-Maroni in French Guiana in case of malaria. Its antioxidant and anti-inflammatory potential, which may help to explain its use against this disease, was demonstrated using models of artificially stimulated cells. Graphical abstract: